Assessment of Product Attributes, Consumer Perceived Value, and Repurchase Intention: A Case of All-You-Can-Eat Beef Buffet - Mujtahidah Anggriani Ummul Muzayyanah; Wahyu Eka Putri (Universitas Pendidikan Ganesha, 2024)
Products with higher attribute values will create higher consumer value perceptions. The higher the perceived value, the higher the consumer's repurchase intention on the product. This study seeks to analyse the effect of product attributes on the consumer's perceived value and intention to repurchase beef dishes at the All-You-Can-Eat (AYCE) buffet. Unrestricted self-selected surveys were conducted with convenience sampling is utilized, and the number of samples obtained is 230 respondents. Structural Equation Modelling (SEM) analysis was used to investigate the effect of the variables. This study reveals that respondents are predominantly female (66.10%) in the range of 18 to 25 years old, and have visited AYCE to buy beef dishes at least one time. The higher the product attributes value, the higher the consumer's perceived value of beef dishes at AYCE buffet (p <0.05). Regarding the intention to repurchase, this study indicated that perceived value and product attributes have a significant positive effect (p <0.05) on consumers' intention to repurchase beef dishes at AYCE buffet. This research highlights the both intrinsic and extrinsic product attributes bring high perceived value and consumer repurchase intentions. The findings of this study recommend marketers for developing effective marketing strategies through adding value to consumers. Differentiation products and making the decision on intrinsic and extrinsic attributes. To compete with similar businesses, product attributes need to be upgraded and given careful consideration.